Framework for Managing the Traffic Impacts of Building Construction Projects - Hyari, Khaled Hesham; Mashaleh, Mohammad S. El; Rababeh, Shaher M. (Penerbit Universiti Sains Malaysia, 2015)
Major building construction projects are important to the economic development of urban areas. However, such projects have negative impacts on their surroundings, particularly on traffic. This paper presents a framework for mitigating the traffic impacts of building construction projects in urban areas. The proposed framework consists of two stages: identification of the logistical construction requirements and development of an impact mitigation plan to control the negative effects of construction traffic on the road network and the surrounding community. The adopted methodology includes (1) a review of the available construction traffic management plans for twenty large building projects worldwide, (2) site visits to seven large building construction projects in urban areas and (3) multidisciplinary focus group sessions to extract knowledge and synthesise the proposed framework for managing the traffic impacts of building construction projects. The suggested framework provides systematic guidance for construction planners and site managers in developing a traffic management and impact mitigation plan for building construction projects. This framework could also help construction planners and site managers to better plan and manage construction activities to minimise the impact on the surrounding roads and minimise unnecessary delays by organising timely movement of resources to and from the construction site.